AN ANALYSIS OF SOURCES ON QURANIC SCIENCES (Modern education and development, 2025)
This article provides a chronological overview of classical sources related to Quranic studies, taking into account the historical periods in which they were composed. It analyzes the structure and scholarly significance of these works, highlighting their gradual development from oral traditions to written compilations. The study also explores the emergence of Quranic sciences as an independent academic discipline, emphasizing the contributions of prominent scholars and key texts in fields such as tafsir, qira’at, and asbab al-nuzul. Additionally, the article discusses the systematic codification of Quranic sciences during the later classical period and notes the decline in new scholarly works after the 15th century. This research serves as a valuable resource for understanding the evolution, organization, and intellectual heritage of Quranic sciences within Islamic scholarship.